A behavioral model framework for an intelligent tutoring system / Ungku Fadhlul Amir Ungku Ibrahim - Ungku Ibrahim, Ungku Fadhlul Amir (Faculty of Information Technology and Quantitative Sciences, 2005)
This research proposes a framework for the behavioural model in an Intelligent Tutoring System. This research intends to investigate the components and elements that are part of the behavioural model. Three components were identified - the Cognitive model, the Knowledge model, and the Psychological model. The elements are categorized into two - Navigational and Operational behaviour. The resulting framework will be integrated into the current Intelligent Tutoring System framework, which typically has a User model. Expert model, Pedagogical model, and a Domain model as its components. This research gathers extensive amount of literatures as the source and idea of the framework designed. During data analysis, it was found that the behavioural model exists in many researches but is implemented in different ways. This research proposes a framework of the behavioural model that centralizes the collection and analysis of behavioural data gathered during the user's interaction with the system. A prototype has been built to test the soundness of the framework, and it provided evidence that the framework is valid. Further studies should be done to enhance the framework. It is recommended that the behaviours of user observed should not be limited to the traditional inputs of keyboards and mice, but the fiiture works should develop a way to observe the overall physical behaviour of the user during the interaction with the system.